Nonviral vectors for gene therapy lipid- and polymer-based gene transfer - Huang, Leaf; Liu, Dexi; Wagner, Ernst, 1960- (Advances in genetics, 2014)
The field of genetics is rapidly evolving, and new medical breakthroughs are occurring as a result of advances in our knowledge of genetics. Advances in Genetics continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines. Includes methods for testing with ethical, legal, and social implications Critically analyzes future directions Written and edited by recognized leaders in the field